1997
DOI: 10.2307/3059723
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Responsibility and Business Regulation: The Case of Sustainable Tourism

Abstract: Original citation: Forsyth, Tim (1997) This document is the author's final manuscript accepted version of the journal article, incorporating any revisions agreed during the peer review process. Some differences between this version and the published version may remain. You are advised to consult the publisher's version if you wish to cite from it. Geographical Journal AbstractThis paper adds to the growing literature within geography on environmental regulation of business activities. The adoption of volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 19 publications
0
40
0
3
Order By: Relevance
“…The UK outgoing tourism industry has introduced sustainable practices, but feared losing competitive position through further adoption (Forsyth, 1997;Curtin and Busby, 1999).…”
Section: Tourism Businesses and Sustainabilitymentioning
confidence: 99%
“…The UK outgoing tourism industry has introduced sustainable practices, but feared losing competitive position through further adoption (Forsyth, 1997;Curtin and Busby, 1999).…”
Section: Tourism Businesses and Sustainabilitymentioning
confidence: 99%
“…However, such policies also change the competitive climate facing the industry and can generate new business opportunities. It is up to each ®rm to respond in the most cost-effective way to these policies, and it has been suggested that the development of proactive strategic policies by ®rms can reduce these costs and establish a competitive advantage (Forsyth, 1997).…”
Section: Government Interventionmentioning
confidence: 99%
“…As discussed above, some critics have questioned how far 'ecotourism' as a current practice generally reflects a rarified and elitist view of nature, rather than the more pragmatic and catholic concern of socalled 'sustainable tourism', which focuses more on the public participation in tourism development, and the environmental impacts of mass, and not just nature-based, tourism (see Cater, 1995;Forsyth, 1997). Under this broader approach to environment and tourism, research is less focused on how consumers construct 'nature' but instead looks more to how tourism may be used long-term and inclusively for sustainable development.…”
Section: Resultsmentioning
confidence: 99%